Experiences of striving to maintain daily life among women with osteoporosis - Carina Nilsson; Birgitta Lindberg; Päivi Juuso; Malin Olsson (International Journal of Qualitative Studies on Health & Well-Being, 2019)
In order to describe how women with osteoporosis strive to maintain daily life we interviewed 11 women using a reflective lifeworld approach based on phenomenological analysis. Osteoporosis is a major public health concern in the Western world, and is predominant among women. Our findings indicated that meanings of striving to maintain daily life imply a belief in oneself and one’s own capabilities. The women expressly speak out for themselves as a way of finding reconciliation without giving in to the illness. Women with osteoporosis expect to gain support early in the course of their illness. They require advice on how to manage the disease as well as support for striving to maintain daily living. Therefore, it is crucial that the women not only are given information about the disease. Equally important is to establish continuity in healthcare encounters, and that health care offers support founded in the women’s lived experiences with focus on their capacities.